Progress in understanding the role and mechanism of miRNAs in osteoporosis - Meng, Feifei; Yang, Changwei; Li, Na; Wang, Huaxin (Frontiers in Endocrinology, 2025)
Osteoporosis is a systemic metabolic disorder characterized by compromised bone strength and increased fracture risk. Exosomes, extracellular vesicles measuring 40–160 nm in diameter, are critical mediators of intercellular communication. Among their bioactive components, microRNAs (miRNAs) have garnered attention for their role in the pathogenesis of Osteoporosis. Through complementary binding to the 3′ untranslated regions of target genes, miRNAs regulate key processes such as bone formation, bone resorption, angiogenesis, and bone immunity. This review provides a comprehensive summary of the regulatory roles and underlying mechanisms of miRNAs in osteoporosis, offering insights into potential therapeutic strategies.